Irrigation Water Potential and Land Suitability Assessment in Kurfa Chele-Girawa Watershed, Wabe Shebelle River Basin, Ethiopia - Girma Mideksa; Tasisa Temesgen Tolossa (Turkish Journal of Agriculture: Food Science and Technology)
Assessing available water and land for irrigation are important for planning their use. In the watershed, stream flows from some of the rivers are not known and potential irrigable areas have not been identified. By delineating watershed boundary, irrigation suitability factors such as soil type, slope, land cover/use, and distance from the water supply were classified based on the FAO guideline for land evaluation in to S1, S2, S3 and N suitability classes independently. The irrigation potential suitability analysis of soil, slope, land cover/use and Euclidean distance indicates that 55.1 %, 95.6 %, 88.6% and 93.7% respectively are in the range of highly to marginally suitable. By weighted overlay analysis, total surface irrigation suitability potential of the study area is 54.6%, from this, the potential irrigable land obtained by multi_ criteria analysis has 45.9%. The total available flow above abstraction site is 335.7m3/s or 2.9-million-meter cube (MMC) annually.